Humidity-thermoelectric bimodal energy harvester for sustainable power generation. (March 2023) - Seo, Byungseok; Han, Hyesu; Kim, Kyungmin; Noh, Dowon; Shim, Joon Hyung; Choi, Wonjoon
Abstract: Thermoelectricity is a promising solution to utilize waste heat for electrical energy, whereas thermal saturation or the temporal absence of thermal gradient incurs discontinuities in energy harvesting. Meanwhile, utilizing humidity has recently emerged as an energy harvesting stimulus owing to its sustainable availability, but its low power output limits feasibility. Herein, we report a humidity-thermoelectric bimodal energy harvester (HT-BET) for sustainable and complementary power generation. Aqueous and air electrothermal wave (ETW) uniformly deposits palladium nitrate precursors and directly fabricates tunable palladium/palladium oxide/carbon-based composites (Pd/Pdx Oy @C) in terms of morphology, composition, and interfacial characteristics, thereby screening optimal electrochemical electrodes for humidity-driven energy-harvesting cells. An asymmetric cell incorporating a solidified poly(4-styrenesulfonic acid) (PSSH) between screened Pd/Pdx Oy @C and carbon fibers is integrated with a thermoelectric p – n junction employing Bi2 Te3 cells to complete the HT-BEH fabrication. The single HT-BEH exhibits highly improved output power by 67 times (0.3 µW), compared with a thermoelectric cell (4.5 nW) at 308.15 K (∆T = 10.35 K) and 30% relative humidity (RH). Furthermore, the flexible multi-array of HT-BEHs achieves 0.41 µW output power for 16 h through the human skin temperature, sweat, and surrounding RH, thereby confirming the capability of sustainable energy sources for wearable platforms in ambient environments. Graphical Abstract: A humidity-thermoelectric bimodal energy harvester enables the complementary power generation to resolve intrinsic restrictions of conventional thermoelectric cells involving the transient absence in power generation and insufficient power level. ga1 Highlights: A humidity-thermoelectric bimodal energy harvester (HT-BEH) offers complementary functions. Aqueous and air electrothermal waves optimize Pd/PdxOy/C electrodes for HT-BEH. Pd/PdxOy/C, Bi2Te3 and PSSH serve as electrode, PN junction, and electrolyte for asymmetric cells. HT-BEH exhibits amplified output power by 67 times compared with a thermoelectric cell. Flexible HT-BEH multi-array attached to human skin achieves sustainable power for 16 h.